AMPK/AS160 mediates tiliroside derivatives-stimulated GLUT4 translocation in muscle cells - Zhang C; Jiang Y; Liu J; Jin M; Qin N; Chen Y; Niu W; Duan H (Dove Medical Press, 2018)
Chang Zhang,1 Yue Jiang,1 Jia Liu,1 Meina Jin,1 Nan Qin,1 Ying Chen,1 Wenyan Niu,2 Hongquan Duan1 1School of Pharmacy, Research Center of Basic Medical Science, Tianjin Medical University, Tianjin 300070, People’s Republic of China; 2Department of Immunology, Key Laboratory of Immune Microenvironment and Disease (Ministry of Education), Key Laboratory of Hormones and Development (Ministry of Health), Tianjin Metabolic Diseases Hospital, Tianjin Medical University, Tianjin 300070, People’s Republic of China Introduction: The Chinese herb Potentilla chinensis can reduce blood glucose level of diabetic mice. Tiliroside is the main effective component, but the detailed mechanism is not clear. Skeletal muscles play an important role in whole body glucose homeostasis. Insulin and exercise/contraction stimulate glucose uptake by muscle cells via redistribution of glucose transporter GLUT4 to the cell surface. Materials and methods: We explored the effects of tiliroside derivatives on cell surface GLUT4 level (GLUT4 translocation) and the underlying mechanism in L6-GLUT4myc muscle cells. Results: We showed that tiliroside derivatives D1–22 stimulated GLUT4myc translocation in L6-GLUT4myc skeletal muscle cells. Derivatives D1, D8 and D18 regulated GLUT4myc translocation in a time- and dose-dependent manner. Their effects on GLUT4 were additive with that of acute insulin stimulation. Moreover, they increased phosphorylated adenosine monophosphate-activated protein kinase (AMPK), but not protein kinase B (PKB, also called Akt). Their effects on GLUT4 were inhibited by Compound C. In addition, derivative D8 significantly stimulated AMPK and Akt substrate of 160 kDa (AS160) phosphorylation and GLUT4myc translocation in L6-GLUT4myc cells, but not in L6-AS160 4A-GLUT4myc cells. Conclusion: Tiliroside derivatives D1, D8 and D18 stimulated GLUT4myc translocation by a mechanism different to that of insulin in skeletal muscle cells. The effect of derivative D8 on GLUT4myc translocation is mediated by AMPK/AS160 signaling pathway. Keywords: type 2 diabetes, skeletal muscle cells, insulin resistance, AMPK